Comparison of Platelet, Leukocyte, and Erythrocyte Levels in Platelet-Rich Plasma with Centrifugation Speeds of 100 g/400 g and 300 g/750 g in Healthy Individuals - Irene Andriani Halim; Ketut Kwartantaya Winaya; Ni Made Dwi Puspawati; I Gusti Nyoman Darmaputra; Nyoman Suryawati; I Gusti Ayu Agung Elis Indira (Faculty of Medicine, Universitas Airlangga, 2026)
Background: Background: Platelet-rich plasma (PRP) is an autologous blood product obtained through centrifugation and is widely applied in dermatology. Its cellular composition—particularly platelet, leukocyte, and erythrocyte levels—is influenced by various centrifugation parameters, with centrifugation speed being a critical factor. Purpose: This study aimed to compare the impact of two different centrifugation speeds, 100 g/400 g and 300 g/750 g, on the cellular composition of PRP. Methods: This cross-sectional study involved collecting blood samples from 34 healthy female subjects aged between 18 and 40 years. The samples were processed into PRP using two centrifugation speeds: 100g/400g (referred to as PRP1) and 300g/750g (referred to as PRP2). The counts of platelets, leukocytes, and erythrocytes were measured before and after centrifugation. Results: The mean platelet count in PRP2 (1,946.76 ± 436.98 × 10³/μL) was significantly higher than in PRP1 (1,445.00 ± 366.34 × 10³/μL; p = 0.000). The mean leukocyte count was significantly greater in PRP1 (58.69±22.82×10³/μL; p = 0.000) compared to PRP2 (32.68±16.20×10³/μL). Erythrocyte contamination was notably lower in PRP1 (0.16 ± 0.06 × 106/μL; p = 0.007) than in PRP2 (0.19 ± 0.06 × 106/μL). Multivariate regression analysis indicated that centrifugation speed was the most significant factor influencing variations in platelet, leukocyte, and erythrocyte counts (p < 0.05), while age and BMI had no significant impact. Conclusion: A centrifugation speed of 300 g/750 g was more effective in increasing platelet concentration but with erythrocyte levels, whereas the 100 g/400 g speed resulted in PRP with a higher leukocyte content.